Clinico-hematological profile and morphological features on bone marrow aspirate in visceral leishmaniasis from non-endemic region - Dr. Arvind Kumar Gupta; Dr. Harish Chandra; Dr. Vandana Bharati; Dr. Neha Singh; Dr. Sanjeev Kishore (Tropical Journal of Pathology and Microbiology, 2019)
Introduction- Leishmaniasis which is caused by Leishmania donovani is considered to be a disease of lowland as climate and geographical factors play an important role in its distribution. However, recently few studies have reported leishmaniasis at higher altitude of Himalayan and sub Himalayan region of India. The present study was therefore conducted to study the clinico- hematological profile and the various morphological features on bone marrow examination associated with leishmaniasis in the non-endemic sub Himalayan region of India. Material and Methods- The study included all the cases of leishmaniasis which were diagnosed on bone marrow examination over a period of one and half year in a medical institute situated in Uttarakhand state of India. Results- The study included total 10 cases of visceral leishmaniasis diagnosed on bone marrow aspirate with fever (10 cases) and hepato-splenomegaly (7 cases) being most common clinical presentation and pancytopenia (9 cases) being the most common haematological finding. Bone marrow aspirate cytology showed that plasmacytosis (9 cases) and hemophagocytosis (8 cases) were the most common features. One case was clinically suspected as acute leukemia which turned out to be a case of leishmaniasis on bone marrow examination. Conclusion- Leishmaniasis is emerging as an important major parasitic infection in the non-endemic Himalayan and sub Himalayan region of India. Fever, splenomegaly and pancytopenia are important clinical and peripheral blood examination features associated with this disease. Hemophagocytosis and plasmacytosis on bone marrow examination should prompt for vigilant search for LD bodies in bone marrow to avoid missing of diagnosis even in unsuspected cases.